A nitrogen-modified nickel tungstate nanorod self-supporting catalyst, a preparation method thereof and application thereof in electrolysis of seawater to produce hydrogen
By growing nitrogen-modified nickel tungstate nanorods on a conductive substrate, an N-NiWO catalyst was prepared, which solved the problem of low hydrogen evolution activity of transition metal nickel tungstate catalysts in seawater electrolysis for hydrogen production, and achieved low-cost and high-efficiency seawater electrolysis for hydrogen production.
Patent Information
- Application Number
- CN202511179493.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-22
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2045-08-22
AI Technical Summary
Existing transition metal nickel tungstate catalysts exhibit low hydrogen evolution activity during seawater electrolysis for hydrogen production, resulting in high costs and making it difficult to meet the demand for low-cost, large-scale hydrogen production.
N-NiWO catalysts were prepared by growing nitrogen-modified nickel tungstate nanorods on a conductive substrate. Urea was used as the nitrogen source for nitrogen modification, which improved the conductivity and catalytic sites of the catalyst and optimized its electronic structure.
It significantly improves the activity and stability of hydrogen production by seawater electrolysis, is low in cost, simplifies the preparation process, and the catalyst exhibits excellent hydrogen evolution performance in seawater electrolysis.
Smart Images

Figure CN120714684B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of electrolysis of seawater catalysts, in particular to a nitrogen-modified tungsten nickel nanorod self-supporting catalyst, a preparation method thereof and application thereof in electrolysis of seawater to produce hydrogen. BACKGROUND
[0002] Energy crisis and environmental problems are two major challenges for the sustainable development of human society, so the development of clean energy is imminent. Among many new energies, hydrogen energy is widely considered as an ideal next-generation clean energy due to its high energy density, wide sources and no pollution emissions, and can produce green hydrogen on a large scale through water electrolysis. Generally, the water electrolysis reaction is divided into two half-reactions of hydrogen evolution and oxygen evolution. At present, noble metal Pt-based catalysts are generally recognized as good hydrogen evolution catalysts. However, noble metal catalysts are not only scarce in reserves, but also expensive in price, which makes it difficult to be widely used. Therefore, it is particularly important to develop earth-abundant and inexpensive electrocatalysts to replace noble metal catalysts to achieve low-cost large-scale hydrogen production.
[0003] Transition metal tungstate (MWO4, where M represents a divalent cation) is a new type of functional material, which contains WO4 2- tetrahedral ions in the crystal structure, and there are many kinds of M divalent cations, so this material has the advantages of uniform distribution of metal ions, high adjustability of components and functions, etc., and is also widely studied in the field of energy storage such as supercapacitors, lithium ion batteries, sodium ion batteries, etc. Among the family of transition metal tungstates, transition metal nickel tungstate (NiWO4) is a classic energy storage material, which is widely studied as a capacitor and battery electrode material, but only a small number of studies have explored its application in water electrolysis.
[0004] In recent years, transition metal nickel tungstate catalysts have gradually attracted the attention and research of researchers due to their good seawater corrosion resistance. However, current researches mostly focus on designing and controlling one-dimensional, two-dimensional or three-dimensional nanostructures of tungsten nickel materials and composite conductive materials to increase the number of active sites and conductivity, thereby improving the catalytic activity. However, the intrinsic hydrogen evolution activity (HER) of the material in electrolysis of seawater and hydrogen production is still low, resulting in high cost of the material in electrolysis of seawater to produce hydrogen. Therefore, based on the low-cost transition metal nickel tungstate catalyst, it is necessary to further improve the hydrogen evolution activity to meet the demand of electrolysis of seawater to produce hydrogen, which is a technical problem to be solved by the present application. SUMMARY
[0005] The purpose of the present application is to solve the problem of how to improve the hydrogen evolution activity of transition metal nickel tungstate catalysts, and to provide a nitrogen-modified tungsten nickel nanorod self-supporting catalyst and a preparation method thereof, and to use the catalyst in electrolysis of seawater to produce hydrogen, thereby meeting the demand of electrolysis of seawater to produce hydrogen.
[0006] To achieve the above object, the present application is realized by the following technical solutions:
[0007] The present application is a nitrogen-modified nickel tungstate nanorod self-supporting catalyst (N-NiWO), which is based on a foam nickel or a nickel mesh as a conductive substrate, wherein a nitrogen-modified nickel tungstate nanorod array is grown on the surface of the conductive substrate.
[0008] The radius of the nitrogen-modified nickel tungstate nanorod in the present application is 500-1800 nm, and the length is 4-15 μm.
[0009] In the present application, the N element in the catalyst is 0.5 %-5 % of the total number of Ni, W, O and N atoms, preferably 1.5 %-3 %.
[0010] The present application also provides a preparation method of a nitrogen-modified nickel tungstate nanorod self-supporting catalyst (N-NiWO), which comprises the following steps:
[0011] (1) Pretreatment: The foam nickel or nickel mesh is first soaked in acid, then washed with water and anhydrous ethanol in sequence, and then naturally air-dried for standby;
[0012] (2) Hydrothermal reaction: The pretreated foam nickel or nickel mesh is used as a substrate, a reaction solution containing nickel ions, tungstate ions and nitrate ions is used, and after hydrothermal reaction, a nickel tungstate catalyst precursor (NiWO) is obtained, which is washed with water and naturally dried for standby;
[0013] (3) Nitrogen modification: In a tube furnace, urea is used as the N source, and the dried nickel tungstate catalyst precursor (NiWO) is modified by chemical vapor deposition at a certain temperature for a period of time, to obtain a nitrogen-modified nickel tungstate nanorod self-supporting catalyst (N-NiWO).
[0014] According to the above scheme, the reaction solution containing nickel ions, tungstate ions and nitrate ions is a deionized aqueous solution of nickel chloride, ammonium tungstate and sodium nitrate, wherein the concentration of nickel chloride is 0.01-0.09 mol / L, the concentration of ammonium tungstate is 0.001-0.009 mol / L, and the concentration of sodium nitrate is 0.01-0.1 mol / L. The temperature of the hydrothermal reaction is 120-180 ℃, and the time is 1-15 h.
[0015] According to the above scheme, the amount of urea used as the N source is 0.1-1.9 g.
[0016] According to the above scheme, the reaction conditions of the tube furnace are as follows: under Ar atmosphere, the temperature is raised to 300-700 ℃ at a rate of 2 ℃ / min and is kept for 1-9 h.
[0017] The application also provides application of the nitrogen-modified nickel tungstate nanorod self-supporting catalyst in electrolysis of seawater to produce hydrogen.
[0018] The application grows the nickel tungstate nanorod on a substrate, and then further modifies the nickel tungstate nanorod by N modification using urea to prepare the N-modified nickel tungstate nanorod self-supporting catalyst (N-NiWO). The nickel tungstate catalyst has the defects of few catalytic active sites and poor intrinsic hydrogen evolution activity. The application designs and constructs the nickel tungstate nanorod self-supporting catalyst on a conductive substrate, which not only improves the conductivity, but also provides a large number of catalytic sites, and further introduces the N element with strong electronegativity to modify and control the electronic structure of the nickel tungstate catalyst, so as to systematically optimize the catalytic performance of the nickel tungstate nanorod in multiple directions. Therefore, the N-modified nickel tungstate nanorod self-supporting catalyst (N-NiWO) has excellent seawater electrolysis hydrogen evolution performance.
[0019] Compared with the prior art, the application has the following advantages:
[0020] 1. The N-modified nickel tungstate nanorod self-supporting catalyst (N-NiWO) has excellent seawater electrolysis hydrogen evolution activity, and the electronic structure of the catalyst is controlled by the nitrogen element, so that the seawater electrolysis HER activity is greatly improved, and the seawater HER stability is excellent.
[0021] 2. The N-NiWO seawater hydrogen evolution catalyst can be prepared by a simple two-step method, and the experimental method is simple and low in cost, which is conducive to the widespread use of the seawater electrolysis hydrogen production. BRIEF DESCRIPTION OF DRAWINGS
[0022] Figure 1 XRD patterns of the N-NiWO and standard NiWO substances synthesized in Example 1 of the application;
[0023] Figure 2 SEM pattern of the N-NiWO synthesized in Example 1 of the application;
[0024] Figure 3 Element line scanning distribution pattern of the N-NiWO self-supporting catalyst synthesized in Example 1 of the application;
[0025] Figure 4 Element face scanning distribution pattern of the N-NiWO self-supporting catalyst synthesized in Example 1 of the application;
[0026] Figure 5 N 1s high-resolution spectrum of the N-NiWO self-supporting catalyst synthesized in Example 1 of the application;
[0027] Figure 6 XRD patterns of the NF and NiWO synthesized in Comparative Example 1 and Comparative Example 2 of the application;
[0028] Figure 7 SEM image of NF synthesized for Inventive Comparative Example 1 ;
[0029] Figure 8 SEM image of NiWO synthesized for Inventive Comparative Example 2;
[0030] Figure 9 Ni 2p high resolution spectra of N-NiWO self-supported catalyst, NiWO catalyst synthesized for Inventive Example 1 and Comparative Example 2;
[0031] Figure 10 W 4f high resolution spectra of N-NiWO self-supported catalyst, NiWO catalyst synthesized for Inventive Example 1 and Comparative Example 2;
[0032] Figure 11 HER polarization curves of different N-NiWO self-supported catalysts synthesized for Inventive Examples 1-3 in alkaline freshwater;
[0033] Figure 12 HER polarization curves of NF, NiWO and N-NiWO catalysts synthesized for Inventive Comparative Examples 1-2 and Inventive Example 1 in alkaline freshwater;
[0034] Figure 13 HER polarization curves of NF, NiWO and N-NiWO catalysts synthesized for Inventive Comparative Examples 1-2 and Inventive Example 1 in alkaline seawater;
[0035] Figure 14 Comparison of overpotential required for HER of N-NiWO self-supported catalyst synthesized for Inventive Example 1 with other reported hydrogen evolution catalysts at 10 mA / cm 2
[0036] Figure 15 Electrochemical double layer capacitance of different catalysts synthesized for Inventive Comparative Examples 1, 2 and Inventive Example 1 ;
[0037] Figure 16 Normalized hydrogen evolution polarization curves of different catalysts synthesized for Inventive Comparative Examples 1, 2 and Inventive Example 1 ;
[0038] Figure 17 Electrochemical impedance spectra of different catalysts synthesized for Inventive Comparative Examples 1, 2 and Inventive Example 1 in alkaline electrolytic seawater;
[0039] Figure 18 Hydrogen evolution stability test of N-NiWO self-supported catalyst synthesized for Inventive Example 1 in alkaline electrolytic seawater;
[0040] Figure 19 Figure of hydrogen evolution performance comparison of N-NiWO self-supported catalyst synthesized for example 1 of the present application before and after multiple cycle tests. DETAILED DESCRIPTION
[0041] In order to understand the technical solutions of the present application, the principles and characteristics of the present application will be described below in combination with specific examples, which are only used to explain the present application and are not used to limit the scope of the present application. Example 1
[0042] The preparation method of the nitrogen-modified nickel tungstate nanorod self-supported catalyst of the present embodiment comprises the following steps:
[0043] (1) Cut the nickel foam (NF) into pieces with a size of 4 cm x 2 cm, then wet the surface with deionized water, then immerse it in a dilute hydrochloric acid solution for ultrasonic treatment for 4-8 min, and then rinse it again with water and ethanol, and then air dry for standby use.
[0044] (2) Use sodium nitrate, ammonium tungstate and nickel chloride to dissolve in deionized water to prepare a hydrothermal reaction solution, wherein the concentration of ammonium tungstate is 0.0045 mol / L, the concentration of nickel chloride is 0.028 mol / L, and the concentration of sodium nitrate is 0.056 mol / L. Put the hydrothermal reaction solution and a piece of treated NF into a 100 mL polytetrafluoroethylene liner, and then put the liner into a stainless steel outer shell of an autoclave, and then treat the autoclave at a temperature of 160 ℃ for 6 h. After the oven cools to room temperature, rinse it alternately with deionized water and ethanol to remove impurities. Then, dry it overnight at 60 ℃ under vacuum atmosphere, and then obtain the nickel tungstate catalyst precursor (NiWO) grown on the NF.
[0045] (3) Weigh 1.0 g of urea (CO(NH2)2) and place it at the gas inlet end of the quartz tube of the tube furnace, and place the prepared NiWO at the middle position of the tube furnace, and then heat it to 500 ℃ at a heating rate of 2 ℃ / min under Ar atmosphere, and then heat it for 2 h, and then cool the tube furnace to room temperature, and then obtain the nitrogen-modified nickel tungstate nanorod self-supported catalyst (N-NiWO) grown on the NF.
[0046] The N-NiWO prepared in the present embodiment is subjected to XRD test, as shown in Figure 1 The diffraction peaks of N-NiWO also have the diffraction peaks of the nickel foam substrate. At the same time, it is found that after nitrogen modification treatment in the tube furnace, the remaining diffraction peaks of N-NiWO correspond to the diffraction peaks of standard substance NiWO4 (PDF # 15-0755), which indicates that no new phase is introduced after calcination and nitrogen modification, and the crystal phase of the nitrogen-modified nickel tungstate nanorod self-supported catalyst is still NiWO4.
[0047] The N-NiWO prepared in the example was subjected to SEM test, as shown in the figure, after nitrogen modification treatment in the tube furnace, the N-NiWO catalyst still had a three-dimensional nanorod structure, the overall morphology was maintained well, and the surface of the calcined nanorod also became rougher. Figure 2
[0048] The N-NiWO prepared in the example was subjected to element line scanning analysis and element area scanning analysis, and the following results were obtained respectively. Figure 3 Figure 4 Figure 3 It can be seen that there is no Ni, W and N element in the blank area, while in a line in the middle part of the nanorod, Ni, W and N elements are clearly present, and it can be observed that the intensity of Ni and W elements is significantly higher than that of N element, indicating that nitrogen element is successfully introduced into the tungsten nickel material; from Figure 4 It can be seen that the three elements of Ni, W and N are uniformly dispersed on the whole nanorod, further indicating that the nitrogen element is uniformly introduced into the tungsten nickel nanorod.
[0049] The N 1s high resolution spectrum of the N-NiWO self-supporting catalyst prepared in example 1 of the application is shown in the figure. Figure 5 In the high resolution XPS spectrum of N, it can be found that after N modification of the NiWO self-supporting catalyst, N-O and N-Ni two XPS peaks are formed, indicating that N element is successfully introduced into the crystal structure of NiWO, and stable chemical bonds are formed with O and Ni therein, so that the modification of N atom can control and optimize the electronic structure of the whole NiWO. Example 2
[0050] The preparation method of the nitrogen modified tungsten nickel nanorod self-supporting catalyst (N-NiWO-0.5) of the example, the specific steps are the same as those of example 1, and the difference lies in that 0.5 g of CO(NH2)2 is weighed as a nitrogen source for modifying the tungsten nickel nanorod self-supporting catalyst in the tube furnace. Example 3
[0051] The preparation method of the nitrogen modified tungsten nickel nanorod self-supporting catalyst (N-NiWO-1.5) of the example, the specific steps are the same as those of example 1, and the difference lies in that 1.5 g of CO(NH2)2 is weighed as a nitrogen source for modifying the tungsten nickel nanorod self-supporting catalyst in the tube furnace.
[0052] Comparative example 1
[0053] For comparison of the effect of the nitrogen-modified tungsten-nickel nanorod self-supported catalyst of the present application with that of the foam nickel on electrolysis of water, the foam nickel (NF) catalyst was prepared as follows: the foam nickel was cut into pieces of 4 cm x 2 cm in size, then the surface was wetted with deionized water, and then immersed in a dilute hydrochloric acid solution for ultrasonic treatment for 4-8 min, and then washed with water and ethanol again, and then naturally air-dried for standby use.
[0054] Comparative Example 2
[0055] For comparison of the effect of the nitrogen-modified tungsten-nickel nanorod self-supported catalyst (N-NiWO) of the present application with that of the tungsten-nickel nanocatalyst (NiWO) on electrolysis of water, the tungsten-nickel nanocatalyst (NiWO) of the present comparative example was prepared by the following steps:
[0056] (1) The foam nickel was cut into pieces of 4 cm x 2 cm in size, then the surface was wetted with deionized water, and then immersed in a dilute hydrochloric acid solution for ultrasonic treatment for 4-8 min, and then washed with water and ethanol again, and then naturally air-dried for standby use;
[0057] (2) A hydrothermal reaction solution was prepared by dissolving sodium nitrate, ammonium tungstate and nickel chloride in deionized water, wherein the concentration of ammonium tungstate was 0.0045 mol / L, the concentration of nickel chloride was 0.028 mol / L, and the concentration of sodium nitrate was 0.056 mol / L. The hydrothermal reaction solution and a piece of treated NF were transferred into a polytetrafluoroethylene liner with a capacity of 100 mL, and the liner was loaded into a stainless steel outer shell of an autoclave, and then the autoclave was treated at a temperature of 160 ℃ for 6 h. After the oven cooled to room temperature, the self-supported catalyst was washed alternately with deionized water and ethanol to remove impurities. After natural drying, the tungsten-nickel nanocatalyst (NiWO) grown on the NF was obtained.
[0058] Figure 6 The XRD pattern of the NF and NiWO synthesized in Comparative Example 1 and Comparative Example 2 is shown in the figure, and the diffraction peaks of the standard Ni substance (PDF #04-0850) are given. As shown in the figure, Figure 6 the diffraction peaks of the NF and NiWO both have the diffraction peaks of the foam nickel substrate. It was found that after the hydrothermal reaction to grow the NiWO, some new peaks appeared in the spectrum of the NiWO, and research and analysis found that the new peaks were derived from the NiWO, corresponding to the diffraction peaks of the standard substance Ni4W6O 21 (OH)2·4H2O (PDF #47-0143), which indicates that the hydrothermal reaction successfully grew the NiWO on the foam nickel substrate.
[0059] Figure 7 The SEM image of the NF catalyst synthesized in Comparative Example 1 is shown in the figure, and the NF has a macroscopic micron-level nickel framework structure. It was found that the surface of the NF was relatively flat, and no nanometer structure catalyst was grown on the surface of the material.
[0060] Figure 8 The SEM image of the catalyst NiWO synthesized for the comparative example 2 is shown in the figure, after the hydrothermal reaction, the smooth surface of the nickel foam grows three-dimensional open nanorods, which are angular cuboid-shaped nanorods, and the research finds that the radius of the nanorod is about 1200 nm, and the length of the nickel tungstate rod is about 11 μm.
[0061] Further, the sample is characterized by using a photoelectron spectrometer (XPS), Figure 9 The Ni 2p high-resolution XPS spectrum of the N-NiWO self-supporting catalyst and the NiWO synthesized for the example 1 and the comparative example 2 of the present application. In the fine XPS spectrum of Ni, it can be found that both samples have Ni 2p 3 / 2 and Ni 2p 1 / 2 Two peaks, and both accompanied by two satellite peaks. By comparing N-NiWO with NiWO, it is found that after N modification, the 2p peak of Ni is shifted to the high valence state by 0.75 eV, indicating that the electrons on Ni in NiWO are transferred to the N atom with stronger electronegativity, thereby indicating that the modification of the N atom regulates and optimizes the electronic structure of the Ni site.
[0062] Figure 10 The W 4f high-resolution XPS spectrum of the N-NiWO and NiWO catalysts synthesized for the example 1 and the comparative example 2 of the present application. From Figure 10 It can be seen that in the fine XPS spectrum of W, it can be found that both samples have W 2p 7 / 2 and W 2p 5 / 2 Two peaks. By comparing N-NiWO with NiWO, it is found that after N modification, the 4f peak of W is shifted to the high valence state by 0.34 eV, indicating that the electrons on W in NiWO are transferred to the N atom with stronger electronegativity, indicating that the modification of the N atom also successfully regulates and optimizes the electronic structure of the W site.
[0063] Application Example
[0064] To highlight the application effect of the N-NiWO catalyst of the present application, the catalysts synthesized in Examples 1-3 and Comparative Examples 1-2 were respectively subjected to seawater electrolysis hydrogen evolution performance test. Material electrochemical test was performed on an AMETEK (USA) PARSTAT MC multi-channel electrochemical analyzer to in-depth study and understand the electrochemical performance of the material. The test adopted a three-electrode system, the working electrode (WE) was respectively the catalyst prepared in Examples 1-3 and Comparative Examples 1-2, the reference electrode (RE) was a Hg / HgO electrode, and the counter electrode (CE) used a carbon rod. The alkaline electrolytic water hydrogen evolution electrolyte was a 1 M KOH deionized water solution (alkaline fresh water), and the alkaline electrolytic seawater hydrogen evolution electrolyte was a 1 M KOH seawater solution (alkaline seawater), and the experiment was performed at room temperature. The voltage obtained by the test was converted into the general reversible hydrogen electrode potential according to the following formula: ERHE = EHg / HgO + 0.0591 x pH + 0.098. The electrochemical hydrogen evolution performance was tested by linear sweep voltammetry (LSV) at 0.09 V~ -0.75 V and a scan rate of 2 mV / s.
[0065] Figure 11 The HER polarization curve graph of the different N-NiWO self-supporting catalysts synthesized in Example 1-3 in alkaline fresh water. It can be clearly found from the graph that the HER activity of the N-NiWO catalyst synthesized under the condition of Example 1 is the best, which only needs an ultra-low overpotential of 66 mV to obtain a 10 mA / cm 2 . At the same time, the N-NiWO prepared in Examples 2 and 3 respectively needs a high overpotential of 107 and 71 mV to obtain the same HER current density.
[0066] Figure 12 The HER polarization curve graph of the NF, NiWO and N-NiWO catalysts synthesized in Comparative Example 1-2 and Example 1 in alkaline fresh water. It can be clearly found from the graph that the HER activity of the N-NiWO self-supporting catalyst synthesized in Example 1 is greatly improved compared with the NF (Comparative Example 1) and NiWO (Comparative Example 2) catalysts. Specifically, in order to output a hydrogen evolution current density of 10 mA / cm 2 , the NF and NiWO respectively need a high overpotential of 177 mV and 149 mV, indicating that nitrogen modification is beneficial to greatly improve the alkaline electrolytic water hydrogen evolution activity of the NiWO self-supporting catalyst.
[0067] Figure 13The graphs show the HER polarization curves of the NF, NiWO, and N-NiWO catalysts synthesized in Comparative Examples 1-2 and Example 1 in alkaline seawater electrolysis. It is clear from the graphs that the N-NiWO self-supporting catalyst synthesized in Example 1 exhibits significantly better HER activity in seawater electrolysis than the NF (Comparative Example 1) and NiWO (Comparative Example 2) catalysts. Specifically, the N-NiWO self-supporting catalyst requires only 90 mV to output 10 mA / cm². 2 The current densities for hydrogen evolution in seawater electrolysis were 177 mV and 149 mV for NF and NiWO, respectively, further indicating that nitrogen modification also significantly improves the hydrogen evolution activity of NiWO self-supporting catalysts in seawater electrolysis.
[0068] Figure 14 The N-NiWO self-supporting catalyst synthesized in Example 1 and other HER catalysts in the literature were compared at 10 mA / cm². 2 The following is a comparison of the required overpotentials. As shown in the figure, the transition metal tungstate seawater HER hydrogen evolution catalysts reported in the literature all require high overpotentials exceeding 80 mV. The N-NiWO self-supporting catalyst in this invention significantly improves the hydrogen evolution performance, requiring only a low overpotential of 66 mV. Therefore, the hydrogen evolution performance of the N-NiWO catalyst in this invention is at an internationally leading level.
[0069] To investigate the mechanism by which the catalyst enhances the activity of the HER process in water electrolysis, we first tested and calculated the electrochemical double-layer capacitance (C0) of the catalyst. dl ), Figure 15 Electrochemical double-layer capacitance (C1) of the NF, NiWO, and N-NiWO catalysts synthesized in Comparative Examples 1-2 and Example 1 dl Generally, the electrochemically active surface area (ECSA) is directly proportional to the electrochemical double-layer capacitance; therefore, the larger the electrochemical double-layer capacitance, the larger the electrochemically active surface area. For example... Figure 15 As shown, N-NiWO has a larger C dl The value reached 30.4 mF / cm. 2 And NF and NiWO's C dl The value is 3.0 mF / cm 2 This indicates that the specific surface area of the catalyst was effectively increased after nitrogen treatment in a tubular furnace.
[0070] Figure 16 The figures show the HER polarization curves of the NF, NiWO, and N-NiWO catalysts synthesized in Comparative Examples 1-2 and Example 1, normalized to their electrochemical active areas. To investigate the intrinsic activity of the catalysts, the hydrogen evolution curves were normalized using the electrochemical active area. Figure 16As shown, the electrolysis water HER of the normalized N-NiWO material is still significantly better than that of NiWO, and the trend of strength and weakness is the same as that before normalization, which indicates that after N modification optimizes the electronic structure of the NiWO catalyst, the intrinsic hydrogen evolution activity of NiWO is greatly improved.
[0071] Figure 17 Electrochemical impedance spectrograms of the NF, NiWO and N-NiWO catalysts synthesized in Comparative Example 1-2 and Example 1 in alkaline seawater. In order to directly study the intrinsic activity of the catalyst, the present application further tests the electrochemical impedance spectrograms of different catalysts. As shown in Figure 6, the electrochemical impedance spectrograms of the NF, NiWO and N-NiWO catalysts in alkaline seawater are shown. Figure 17 As shown, the interface charge transfer resistance semicircle of the N-NiWO material is found to be the smallest, only 1.2 Ω, which indicates that the intrinsic hydrogen evolution activity of the N modified NiWO is greatly improved, and the interface charge transfer of the hydrogen evolution reaction is more rapid.
[0072] Figure 18 is a stability test diagram of the N-NiWO self-supporting catalyst prepared under the conditions of Example 1 in alkaline seawater electrolyte at a large current density of 100 mA / cm 2 As can be seen from the figure, the hydrogen evolution voltage curve of the N-NiWO self-supporting catalyst is basically unchanged in 100 h of work, indicating that the N-NiWO self-supporting catalyst has good alkaline electrolytic seawater hydrogen evolution stability.
[0073] Figure 19 is the seawater hydrogen evolution polarization curve of the N-NiWO self-supporting catalyst prepared under the conditions of Example 1 before and after 1000 cycles of seawater hydrogen evolution. It is found that the seawater hydrogen evolution performance curves of the catalyst before and after the seawater hydrogen evolution stability test are nearly coincident, further indicating that the N-NiWO self-supporting catalyst has excellent electrolytic seawater hydrogen evolution stability.
[0074] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A nitrogen-modified self-supported nickel tungstate nanorod catalyst, characterized in that: The catalyst is a conductive substrate of nickel foam or nickel mesh, wherein a nitrogen-modified nickel tungstate nanorod array is grown on the surface of the conductive substrate; In the preparation, the following steps are included: (1) Pretreatment: the nickel foam or nickel mesh is first soaked in acid, then washed with water and anhydrous ethanol in sequence, and naturally dried for standby; (2) Hydrothermal reaction: the pretreated nickel foam or nickel mesh is used as a substrate, a reaction solution containing nickel ions, tungstate ions and nitrate ions is used, and a nickel tungstate catalyst precursor is obtained after hydrothermal reaction, and then washed with water and naturally dried for standby; (3) Nitrogen modification: in a tube furnace, urea is used as a N source, the reaction conditions of the tube furnace are as follows: the temperature is raised to 300-700 ℃ at a rate of 2 ℃ / min under Ar atmosphere and kept for 1-9 h, and the dried nickel tungstate catalyst precursor is modified by chemical vapor deposition, thereby obtaining a nitrogen-modified nickel tungstate nanorod self-supporting catalyst.
2. The nitrogen-modified self-supported nickel tungstate nanorod catalyst according to claim 1, characterized in that: The radius of the nitrogen-modified nickel tungstate nanorod is 500-1800 nm, and the length is 4-15 μm.
3. The nitrogen-modified self-supported nickel tungstate nanorod catalyst according to claim 1 or 2, characterized in that: The N element in the catalyst is 0.5 %-5 % of the total number of atoms of Ni, W, O and N.
4. The nitrogen-modified self-supported nickel tungstate nanorod catalyst according to claim 3, characterized in that: The N element in the catalyst is 1.5 %-3 % of the total number of atoms of Ni, W, O and N.
5. The nitrogen-modified self-supported nickel tungstate nanorod catalyst according to claim 1, characterized in that: The reaction solution containing nickel ions, tungstate ions and nitrate ions is a deionized aqueous solution of nickel chloride, ammonium tungstate and sodium nitrate, wherein the concentration of nickel chloride is 0.01-0.09 mol / L, the concentration of ammonium tungstate is 0.001-0.009 mol / L, the concentration of sodium nitrate is 0.01-0.1 mol / L, the hydrothermal reaction temperature is 120-180 ℃, and the time is 1-15 h.
6. The nitrogen-modified self-supported nickel tungstate nanorod catalyst according to claim 1, characterized in that: The amount of the N source urea used is 0.1-1.9 g.
7. Use of the nitrogen-modified nickel tungstate nanorod self-supporting catalyst in the electrolysis of seawater to produce hydrogen.
Citation Information
Patent Citations
Preparation of self-supporting nickel-cobalt tungsten molybdenum sulfide electrocatalyst and application of electrocatalyst in hydrogen production by electrolysis of water
CN118756208A
KR20250009284A